Классовый анализ в современной социологии - Макеев, С. (Социология: теория, методы, маркетинг, 2001)
Class analysis is studied as actual branch of sociological interpretation of social world opposite to any tendencies of its homogenization. As elements of economic order, classes are meant to be top-individual class positions. Sociological concept of classes deals with the concepts of inequality, class action and conflicts, as well as with historically subsequent formation of class identity, transformation from “class being inside itself into a class for itself” (K.Marx). Class identity is presented as a habitualised ability to perceive existing social diversities.